A mechanochemical method for preparing fumarate-based metal-organic framework materials

The ball milling of disodium fumarate, metal salt and N,N-dimethylformamide in a ball milling tank by force chemistry method, solving the problems of high energy consumption and low specific surface area when synthesizing fumarate-based MOF materials in the prior art, and achieving efficient and environmentally friendly preparation of high specific surface area MOF materials.

CN118325107BActive Publication Date: 2025-02-28GUANGDONG CARBON LANGUAGE NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410431141.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-11
Publication Date
2025-02-28
Estimated Expiration
2044-04-11

AI Technical Summary

Technical Problem

The prior art has problems in the synthesis of fumarate-based MOF materials, such as the use of a large number of organic solvents, high pressure and high temperatures, high energy consumption, high equipment requirements and small specific surface area.

Method used

Using force chemistry, disodium fumarate, metal salt and trace amount of N,N-dimethylformamide were added to the ball mill for ball milling, and a high specific surface area fumarate MOF material was generated through coordination reaction.

Benefits of technology

It has achieved green and environmentally friendly, normal temperature and pressure reaction, simple and efficient, fast reaction, low cost, high yield and high specific surface area preparation, and overcomes various shortcomings of the traditional method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
  • Figure 00000000_0001_ABST
    Figure 00000000_0001_ABST
Patent Text Reader

Abstract

The present invention relates to a mechanochemical method for preparing metal-organic framework (MOF) materials, and belongs to the technical field of MOF materials. Disodium fumarate, metal salt, and trace N, N-dimethylformamide are added to a ball mill, and ball milling is performed to make the metal ions react with fumarate to generate a fumaric acid-based MOF material with a high specific surface area. Trace N, N-dimethylformamide can accelerate the coordination reaction, while acting as a template and increasing the specific surface area of ​​the fumaric acid-based material. The present invention uses a mechanochemical method to convert disodium fumarate and metal salt into fumaric acid-based MOF materials, which has the advantages of green environmental protection, low cost, high yield and high specific surface area, and not only provides a new idea for synthesizing fumaric acid-based MOF materials at room temperature, but also provides a new strategy for the industrial preparation of fumaric acid-based MOF materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal-organic framework (MOF) materials, and in particular relates to a mechanochemical method for preparing a fumaric acid-based metal-organic framework material. Background Art

[0002] MOF is a type of porous crystalline material formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds. It has broad application prospects in gas adsorption and separation, catalysis, photoelectric conversion and biomedicine. Fumaric acid-based MOFs materials are usually framework materials formed by fumarate bridges with trivalent or tetravalent metal ions as inorganic units. They have the characteristics of rich pore structure, good water stability and chemical stability, and have important applications in adsorption, separation and catalysis. At present, the main methods for synthesizing fumaric acid-based MOFs are solvothermal method, solution reflux method and mechanical ball milling method.

[0003] Mani Ganesh et al. dissolved 1.55mmol fumaric acid and 0.517mmol zirconium chloride in 20mL DMF, then transferred the mixture to a polytetrafluoroethylene-lined stainless steel autoclave, heated at 120°C for 24 hours, and then cooled naturally to room temperature. The resulting white solid was filtered, washed several times with N,N-dimethylformamide and ethanol to remove unreacted substances, and finally dried in an oven at 70°C for 24 hours. After exchanging with CHCl3 three times every 12 hours, Zr-MOF was obtained by vacuum drying at 100°C (Mani Ganesh, Pushparaj Hemalatha, Mei Mei Peng, Wang Seog Cha, Hyun Tae Jang. Zr-fumarate MOF a novel CO2-adsorbing material: Synthesis and characterization. Aerosol and Air Quality Research, 2014, 14(6): 1605-1612). The disadvantages of this solvothermal method are as follows: (1) it requires the use of a large amount of organic solvents N,N-dimethylformamide and ethanol; (2) it requires high pressure (generally 10 to 80 bar) and high temperature (e.g. 120°C), which places high demands on equipment; (3) it takes a long time to react (e.g. 24 hours) and consumes a lot of energy.

[0004] Lin Zhou et al. dissolved 0.9g fumaric acid and 0.45g sodium aluminate in 50mL water and used a 90°C water bath to synthesize 0.64g aluminum fumarate MOF (Lin Zhou, Xinghua Zhang, Yunlin Chen. Facile synthesis of Al-fumarate metal-organic framework nano-flakes and their highly selective adsorption of volatile organic compounds. Materials Letters, 2017, 197, 224-227). This method overcomes the disadvantages of using organic solvents in the solvothermal method, but it still has some shortcomings: (1) It needs to be heated to 90°C for reflux, which consumes a lot of energy; (2) Fumaric acid solution is corrosive at high temperatures and is easy to corrode equipment; (3) Fumaric acid has a low solubility in water, so a large amount of water is needed as a solvent (78.1mL of water is needed to synthesize 1g of fumaric acid-based MOF), resulting in the generation of a large amount of wastewater.

[0005] Mechanochemical method refers to the direct reaction of metal salts and organic ligands by mechanical grinding to make all the components evenly mixed, and then react at a specific temperature to form MOF materials. Mechanochemical method can not only reduce the pollution of solvent volatilization to the environment and save costs, but also synthesize MOF materials in large quantities. It has been widely used in MOF synthesis recently. Haneul Jeong et al. placed 2.7g of ferric chloride hexahydrate and 1.6g of disodium fumarate in a mortar and then ground the mixture for 10 minutes. The final product was washed twice with deionized water and acetone, and 1.5g of Fe-MOF was obtained after drying (Haneul Jeong, Junhyung Lee. 3D-Superstructured networks comprising Fe-MIL-88A metal-organic frameworks under mechanochemical conditions. European Journal of Inorganic Chemistry, 2019, 2019 (42), 4597-4600). The disadvantage of this method is that the specific surface area is less than 110m 2 / g. Therefore, there is an urgent need for a method for preparing a fumaric acid-based MOF material with a high specific surface area that is green, environmentally friendly, reacts at room temperature and pressure, is simple, efficient, rapid, low-cost and has a high yield. Summary of the invention

[0006] The purpose of the present invention is to provide a mechanochemical method for preparing a fumaric acid-based metal-organic framework material, which has the advantages of being green and environmentally friendly, rapid reaction, low cost, high yield and high specific surface area.

[0007] In order to achieve the above object, the present invention adopts the following scheme:

[0008] The present invention provides a mechanochemical method for preparing a fumaric acid-based metal-organic framework material, the method comprising:

[0009] Step 1: adding disodium fumarate, metal salt and N,N-dimethylformamide into a ball mill and performing ball milling to obtain a product;

[0010] Step 2: Wash and dry the product obtained in step 1 to obtain a fumaric acid-based metal-organic framework material.

[0011] Preferably, the metal salt in step 1 is one or more of aluminum chloride, zirconium chloride, zinc chloride, calcium chloride, copper sulfate, manganese chloride or nickel chloride hexahydrate.

[0012] Preferably, the molar ratio of the metal element to disodium fumarate in the metal salt in step 1 is (0.33-1):1.

[0013] Preferably, the ratio of the volume mL of N,N-dimethylformamide described in step 1 to the mass and g of the metal salt and disodium fumarate in the raw material is 0.10-0.25 mL / g.

[0014] Preferably, the ball milling speed in step 1 is 200 to 600 rpm.

[0015] Preferably, the ball milling time in step 1 is 2 to 5 hours.

[0016] Beneficial effects of the present invention

[0017] (1) Compared with the traditional solvothermal method, the present invention does not use a large amount of organic solvent, operates at normal pressure and room temperature, has low requirements on equipment, has a short reaction time, low energy consumption, and is easy to scale up.

[0018] (2) Compared with the traditional solution reflux method, the present invention does not use heating reflux, has low requirements on equipment, and does not generate a large amount of wastewater.

[0019] (3) Compared with the traditional mechanochemical method, the present invention adds a trace amount of N,N-dimethylformamide and performs ball milling to make the metal ions react with fumarate to generate a fumaric acid-based MOF material with a high specific surface area. The trace amount of N,N-dimethylformamide accelerates the coordination reaction and acts as a template to increase the specific surface area of ​​the fumaric acid-based MOF material (up to 512 to 865 m 2 / g). The present invention is a method for preparing a fumaric acid-based MOF material with a high specific surface area, which is green, environmentally friendly, reacts at room temperature and pressure, is simple, efficient, has a rapid reaction, is low-cost, has a high yield and has a high specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The X-ray diffraction spectrum and scanning electron microscope image of the Al-MOF material synthesized by disodium fumarate and aluminum chloride in Example 1 of the present invention.

[0021] Figure 2 These are the X-ray diffraction spectrum and scanning electron microscope image of the Zr-MOF material synthesized from disodium fumarate and zirconium chloride in Example 2 of the present invention.

[0022] Figure 3 The X-ray diffraction spectrum and scanning electron microscope image of the Zn-MOF material synthesized by disodium fumarate and zinc chloride in Example 3 of the present invention.

[0023] Figure 4 The X-ray diffraction spectrum and scanning electron microscope image of the Ca-MOF material synthesized from disodium fumarate and calcium chloride in Example 4 of the present invention.

[0024] Figure 5 The X-ray diffraction spectrum and scanning electron microscope image of the Cu-MOF material synthesized from disodium fumarate and copper sulfate in Example 5 of the present invention.

[0025] Figure 6 These are the X-ray diffraction spectrum and scanning electron microscope image of the Mn-MOF material synthesized from disodium fumarate and manganese chloride in Example 6 of the present invention.

[0026] Figure 7 The X-ray diffraction spectrum and scanning electron microscope image of the Ni-MOF material synthesized by disodium fumarate and nickel chloride hexahydrate in Example 7 of the present invention.

[0027] Figure 8 This is the X-ray diffraction spectrum of the synthetic material of disodium fumarate and aluminum chloride in Comparative Example 1. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0029] The present invention provides a mechanochemical method for preparing a fumaric acid-based metal-organic framework material, the method comprising:

[0030] Step 1: Add disodium fumarate, metal salt and N,N-dimethylformamide into a ball mill for ball milling to obtain a product; the molar ratio of the metal element in the metal salt to disodium fumarate is preferably (0.33-1):1; the ratio of the volume mL of the N,N-dimethylformamide to the mass and g of the metal salt and disodium fumarate in the raw material is 0.10-0.25mL / g; the metal salt is preferably one or more of aluminum chloride, zirconium chloride, zinc chloride, calcium chloride, copper sulfate, manganese chloride or nickel chloride hexahydrate. The ball milling speed is preferably 200-600 rpm, more preferably 300-400 r / min; the ball milling time is preferably 2-5h, more preferably 3-4h.

[0031] Step 2: Wash and dry the product obtained in step 1 to obtain a fumaric acid-based metal-organic framework material.

[0032] The present invention adds disodium fumarate, metal salt and trace N,N-dimethylformamide into a ball milling tank, performs ball milling, and makes the metal ions react with fumarate to generate a fumaric acid-based MOF material with a high specific surface area. The trace N,N-dimethylformamide can accelerate the coordination reaction, and at the same time act as a template, introduce a more porous structure, and increase the specific surface area of ​​the fumaric acid-based material.

[0033] The present invention is further described in detail below with reference to specific examples, and the raw materials involved in the examples are all commercially available.

[0034] Example 1

[0035] 10.00g disodium fumarate, 8.33g aluminum chloride and 2.75mL N,N-dimethylformamide were added to the ball mill. That is, the molar ratio of aluminum element in aluminum chloride to disodium fumarate is 1, and the ratio of the volume of solvent N,N-dimethylformamide (mL) to the mass of raw materials disodium fumarate and aluminum chloride (g) is 0.15mL / g. Ball milling was performed at a speed of 400r / min for 2h. After that, the product was taken out, and after washing and drying, 10.02g Al-MOF material was obtained, with a yield of 98wt%.

[0036] Figure 1 a is the X-ray diffraction spectrum of Al-MOF material, Figure 1 b is a scanning electron microscope image of Al-MOF material. From the X-ray diffraction spectrum, it can be seen that Al-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Al-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular, with a lamellar structure and a size of tens of nanometers. Further results show that the specific surface area of ​​Al-MOF material is 865m 2 / g.

[0037] Example 2

[0038] 13.00g disodium fumarate, 6.25g zirconium chloride and 1.85mL N,N-dimethylformamide were added to the ball mill. That is, the molar ratio of zirconium element to disodium fumarate in zirconium chloride is 0.33, and the ratio of the volume (mL) of solvent N,N-dimethylformamide to the mass and g of raw materials disodium fumarate and zirconium chloride is 0.10mL / g. Ball milling was performed at a speed of 200r / min for 2h. After that, the product was taken out, and after washing and drying, 12.03g Zr-MOF material was obtained, with a yield of 89%.

[0039] Figure 2 a is the X-ray diffraction spectrum of Zr-MOF material, Figure 2 b is a scanning electron microscope image of the Zr-MOF material. From the X-ray diffraction spectrum, it can be seen that the Zr-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Zr-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular and has a network structure. Further results show that the specific surface area of ​​the Zr-MOF material is 714m 2 / g.

[0040] Example 3

[0041] Add 10.00g disodium fumarate, 8.52g zinc chloride and 2.26mL N,N-dimethylformamide to the ball mill. That is, the molar ratio of zinc element in zinc chloride to disodium fumarate is 1, and the ratio of the volume of solvent N,N-dimethylformamide (mL) to the mass of raw materials disodium fumarate and zinc chloride (g) is 0.12mL / g. Ball mill at a speed of 300r / min for 4h. Then take out the product, wash and dry it to obtain 12.65g Zn-MOF material with a yield of 88%.

[0042] Figure 3 a is the X-ray diffraction spectrum of Zn-MOF material, Figure 3 b is a scanning electron microscope image of the Zn-MOF material. From the X-ray diffraction spectrum, it can be seen that the Zn-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Zn-MOF. From the scanning electron microscope image, it can be seen that the material morphology is a long sheet structure. Further results show that the specific surface area of ​​the Zn-MOF material is 725m 2 / g.

[0043] Example 4

[0044] Add 10.00g disodium fumarate, 6.93g calcium chloride and 2.54mL N,N-dimethylformamide to the ball mill. That is, the molar ratio of calcium element in calcium chloride to disodium fumarate is 1, and the ratio of the volume of solvent N,N-dimethylformamide (mL) to the mass of raw materials disodium fumarate and calcium chloride (g) is 0.15mL / g. Ball mill at a speed of 400r / min for 3h. Then take out the product, wash and dry it to obtain 10.40g Ca-MOF material with a yield of 94%.

[0045] Figure 4 a is the X-ray diffraction spectrum of Ca-MOF material, Figure 4 b is a scanning electron microscope image of the Ca-MOF material. From the X-ray diffraction spectrum, it can be seen that the Ca-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Ca-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular, with a flaky structure and a size ranging from tens of nanometers to several microns. Further results show that the specific surface area of ​​the Ca-MOF material is 595m 2 / g.

[0046] Example 5

[0047] Add 10.00g disodium fumarate, 8.98g copper sulfate and 4.50mL N,N-dimethylformamide into a ball mill. That is, the molar ratio of copper element in copper sulfate to disodium fumarate is 1, and the ratio of the volume (mL) of solvent N,N-dimethylformamide to the mass and g of raw materials disodium fumarate and copper sulfate is 0.25mL / g. Ball mill at a speed of 200r / min for 3h. Then take out the product, wash and dry it to obtain 10.01g Cu-MOF material with a yield of 89wt%.

[0048] Figure 5 a is the X-ray diffraction spectrum of Cu-MOF material, Figure 5 b is a scanning electron microscope image of the Cu-MOF material. From the X-ray diffraction spectrum, it can be seen that the Cu-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Cu-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular, with a spherical structure with a diameter of 3 to 13 μm, and the spherical structure is composed of smaller rectangular blocks. Further results show that the specific surface area of ​​the Cu-MOF material is 625m 2 / g.

[0049] Example 6

[0050] 10.00g disodium fumarate, 7.86g manganese chloride and 2.68mL N,N-dimethylformamide were added to the ball mill. That is, the molar ratio of manganese element in manganese chloride to disodium fumarate is 1, and the ratio of the volume (mL) of solvent N,N-dimethylformamide to the mass and g of raw materials disodium fumarate and manganese chloride is 0.15mL / g. Ball milling was performed at a speed of 500r / min for 4h. After that, the product was taken out, and after washing and drying, 10.3g Mn-MOF material was obtained, with a yield of 86wt%.

[0051] Figure 6 a is the X-ray diffraction spectrum of Mn-MOF material, Figure 6 b is a scanning electron microscope image of the Mn-MOF material. From the X-ray diffraction spectrum, it can be seen that the Mn-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Mn-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular, with a nanoparticle structure and a size of tens of nanometers. Further results show that the specific surface area of ​​the Mn-MOF material is 585m 2 / g.

[0052] Example 7

[0053] Add 10.00g disodium fumarate, 14.85g nickel chloride hexahydrate and 5.10mL N,N-dimethylformamide into a ball mill. That is, the molar ratio of nickel element to disodium fumarate in nickel chloride hexahydrate is 1, and the ratio of the volume (mL) of solvent N,N-dimethylformamide to the mass and (g) of raw materials disodium fumarate and nickel chloride hexahydrate is 0.21mL / g. Ball mill at a speed of 600r / min for 5h. Then take out the product, wash and dry it to obtain 11.90g Ni-MOF material with a yield of 97wt%.

[0054] Figure 7 a is the X-ray diffraction spectrum of Ni-MOF material, Figure 7 b is a scanning electron microscope image of Ni-MOF material. From the X-ray diffraction spectrum, it can be seen that Ni-MOF material has significant characteristic diffraction peaks, indicating the successful synthesis of Ni-MOF. From the scanning electron microscope image, it can be seen that the material morphology is relatively regular, with a flaky structure and a size of tens of nanometers. Further results show that the specific surface area of ​​Ni-MOF material is 512m 2 / g.

[0055] Comparative Example 1

[0056] 10.00g disodium fumarate and 8.33g aluminum chloride were placed in a ball mill. That is, the molar ratio of aluminum element in aluminum chloride to disodium fumarate was 1. The ball mill was performed at a speed of 400r / min for 2h. After that, the product was taken out, and after washing and drying, 5.33g of sample material was obtained, with a yield of 43wt%.

[0057] Figure 8 is the X-ray diffraction spectrum of the material. From the X-ray diffraction spectrum, it can be seen that the product does not have the significant characteristic diffraction peak of Al-MOF, indicating that Al-MOF was not successfully synthesized. Further results show that the specific surface area of ​​the product is 42m 2 / g.

[0058] Comparative Example 2

[0059] 10.00g disodium fumarate, 8.33g aluminum chloride and 2.75mL ethanol were added to the ball mill. That is, the molar ratio of aluminum element in aluminum chloride to disodium fumarate is 1, and the ratio of the volume of solvent ethanol (mL) to the mass of raw materials disodium fumarate and aluminum chloride (g) is 0.15mL / g. Ball milling was performed at a speed of 400r / min for 2h. After that, the product was taken out, and after washing and drying, 5.89g Al-MOF material was obtained, with a yield of 48wt%.

Claims

1. A mechanochemical method for preparing a fumarate-based metal-organic framework material, characterized in that: The method includes: Step 1: adding disodium fumarate, metal salt and N,N-dimethylformamide into a ball mill and performing ball milling to obtain a product; Step 2: washing and drying the product obtained in step 1 to obtain a fumaric acid-based metal-organic framework material; The ratio of the volume mL of N,N-dimethylformamide described in step 1 to the mass and g of the metal salt and disodium fumarate in the raw material is 0.10-0.25 mL / g.

2. A mechanochemical method for preparing a fumarate-based metal-organic framework material according to claim 1, characterized in that: The metal salt described in step 1 is one or more of aluminum chloride, zirconium chloride, zinc chloride, calcium chloride, copper sulfate, manganese chloride or nickel chloride hexahydrate.

3. A mechanochemical method for preparing a fumarate-based metal-organic framework material according to claim 1, characterized in that: The molar ratio of the metal element to disodium fumarate in the metal salt described in step 1 is (0.33-1):

1.

4. A mechanochemical method for preparing a fumarate-based metal-organic framework material according to claim 1, characterized in that: The ball milling speed in step 1 is 200 to 600 rpm.

5. A mechanochemical method for preparing a fumarate-based metal-organic framework material according to claim 1, characterized in that: The ball milling time in step 1 is 2 to 5 hours.

Citation Information

Patent Citations

  • Separation method of 1,3-butadiene and separation membrane

    JP2014088341A

  • Metal organic frameworks and methods of making and using same

    US20190217270A1